INCREASING THE COMPETITIVENESS AND ECONOMIC EFFICIENCY OF THE TEXTILE INDUSTRY THROUGH IMPLEMENTATION OF INNOVATIVE TECHNOLOGIES (Marketing Journal, 2025)
The article evaluates the economic efficiency of implementing innovative technologies in the textile industry. The impact of technological solutions on production efficiency, cost reduction, and product quality was examined. The improvement of competitiven ess through Industry 4.0 technologies –particularly IoT, artificial intelligence, and automation –was substantiated. A comparative analysis with international experience was conducted, and conclusions were adapted to Uzbekistan's context. Financial risks, wo rkforce shortages, and infrastructure gaps were identified № 1 175 as key limitations. Recommendations were made to accelerate technological transformation.
Keywords: textile industry; innovative technologies; economic efficiency; Industry 4.0; IoT; competitiveness